The Influence of Self-Regulation Behaviors on University Students’ Intentions of Persistance - Bernardo, Ana; Esteban, María; Cervero, Antonio; Cerezo, Rebeca; Herrero, Francisco Javier (Frontiers in Psychology, 2019)
The implementation of the European Higher Education Area is a true paradigm change in university education in which the student, with particular consideration given to autonomous work, takes the place of the teacher as the central element of the teaching-learning process. In this autonomous work, the strategies the students regularly use become particularly important, given the supposition that doing that work will lead to academic success. The objective of this study is to analyze the variables that influence students’ expectations of success, measured through their intention to persist on the course they are doing. A questionnaire designed ad hoc was given to a sample of 1037 university students. It included aspects related to reasons for choosing the course, institutional integration, use of self-regulation strategies, and intention to drop out. Data analysis allowed the identification of satisfaction with the course chosen and appropriate study skills acquired in secondary education as predictors of expectations of academic persistence, with some differences in terms of gender. Other strategies such as class attendance or going deeply into course content did not figure. These results are at odds with the principles underlying the European Higher Education Area and show that they have not yet been interiorized by the students, who continue to perceive their studies more traditionally.